Global Value Chains and Export-Import Determinants in the European Union Member Countries - MIRDALA, Rajmund (Journal of Advanced Research in Law and Economics, 2018)
Intra-Eurozone current account imbalances represent one of the most discussed topics related to the competitiveness issues of the common currency area since its establishment. Many authors examined this phenomenon considering possible linkages to effects of common monetary policy, real exchange rates movements, variety of demand drivers (fiscal imbalances included) and capital flows. However, as a result of increasing specialization on the individual country level during past few decades that stimulated distribution of individual stages of production across countries, dynamics of exports and imports of final goods, intermediate goods as well as primary inputs was associated with generally ambiguous effect on the external balance. The paper investigates the main determinants of disaggregated export and import demand functions on the sample of 21 the European Union member countries. Our results from estimated ARDL model based on the panel data indicates relatively significant importance of intermediate goods in the formation of external trade balances within as well as outside European Union from both territorial and commodity aspects.